(untitled) - Susskind, Charles (Baltimore, 1973)
Contents: A curious deficiency besets our society. Educated and well-read citizens, no matter how specialized their education and reading, know a good deal about traditional culture. In America, even engineering students must complete a prescribed number of college courses in socio-humanistic studies.
Keywords: Technology,Công nghệ